Response of Islamic Education Students at As'adiyah Islamic University Towards the Use of Digital Technology in The Learning Process - Umrati, Umrati; Muhsyanur, Muhsyanur; Ardianto, Ardianto; Hardi Yanti, Hardi Yanti (ETDC: Indonesian Journal of Research and Educational Review, 2023)
This study aims to analyze the response of Islamic Religious Education students at As'adiyah Islamic University to the use of digital technology in the learning process. With the development of technology, the integration of digital media in education is very important to increase the effectiveness and efficiency of learning. The research method used is qualitative with a phenomenological approach, which aims to understand students' experiences and views in depth. Data were collected through in-depth interviews and participatory observation with 115 purposively selected data sources. The results of the study show that students have a positive response to the use of digital technology in learning. They acknowledge that digital technologies, such as online learning platforms, learning videos, and educational apps, have helped them understand the material better and make the learning process easier. From the results of this study, it can be concluded that the use of digital technology has great potential to improve the quality of learning in the Islamic Religious Education environment, although technical support is still needed for students so that they can make maximum use of technology. This research is expected to provide input for curriculum development and learning strategies at As'adiyah Islamic University.